Possible involvement of single nucleotide polymorphisms in anti-Müllerian hormone signaling pathway in the pathogenesis of early OHSS in Han Chinese women - Wang, Lan (Int J Clin Exp Pathol, 2015)
To investigate the possible relationship between single nucleotide polymorphisms (SNPs) in the anti-Müllerian hormone (AMH) signaling pathway and the incidence of early OHSS, the genomic DNA was isolated from peripheral blood leukocytes of 122 participants (62 patients with early OHSS and 60 patients without OHSS who underwent IVF/ICSI), and SNPs of the AMH and AMHR2 exons were detected directly. Further more, genotype distribution and allele frequency were analyzed. We found seven types of SNPs in the AMH exons, and two of them were missense mutations (rs10407022 and rs182295886). However, these two missense mutations did not increase the risk of early OHSS (rs10407022, P=0.307, OR=1.552, CI 0.668, 3.608; rs182295886, P=0.442, OR=0.359, CI 0.026, 4.883). While it was observed that participants with the SNP (rs10407022) had a relatively higher ovarian response than those without the SNP. Further more, we did not find any SNPs in exons of AMHR2. In conclusion, we analyzed the pathogenesis of OHSS by first investigating the SNPs in the AMH signaling pathway. There is no association between SNPs in the AMH/AMHR2 signaling pathway and early OHSS in Han Chinese women.